A phase II trial of temozolomide (TMZ) 1 week on/1 week off as initial treatment for high risk low grade oligodendroglial tumors: An AINO (Italian Association for Neuro-Oncology) study. - Roberta Ruda; Alessia Pellerino; Federica Franchino; Andrea Pace; Carmine Maria Carapella; Cristina Dealis; Manuela Caroli; Marina Faedi; Chiara Bomprezzi; Riccardo Soffietti (Journal of Clinical Oncology, 2017)
2026 Background: The efficacy of dose-dense temozolomide (TMZ, 1 week on/1 week off ) in grade II gliomas is not well known and could depend on the molecular subtype. Methods: Between 2006 and 2010 a single arm phase II study on 60 patients with grade II oligodendroglial tumors was performed. Inclusion criteria were as follows: 1) age ≥ 18 years; 2) KPS ≥ 70; 3) biopsy-proven grade II oligodendroglioma or oligoastrocytoma ; 4) a measurable residual tumor after surgery. The primary endpoint was tumor response on MRI according to RANO criteria, while the secondary endpoints were progression-free survival (PFS), overall survival (OS), and seizure control. Most patients (65%) had seizures. Molecular factors (IDH 1-2 mutations, 1p19q codeletion, MGMT methylation) were available in 49/60 patients (81.7%). The median number of cycles was 11 (2-18). Median follow up was 64 months (7-112). Results: Response rate was PR in 21/60 (35%) patients, minor PR (mPR) in 14/60 (23%), SD in 21/60 (35%) and PD in 4/60 (7%). Most patients achieved the best tumor response within 6 months after the start of TMZ. Among patients with mPR and PR, 15/49 (30.6%) were IDH1-2 mutated with a PFS of 71.4% at 36 months and 28.6% at 60 months with a median value of 46 months while 11/49 (22.4%) were IDH 1-2 wild-type with a PFS of 45.8% at 36 months and 25% at 60 months with a median value of 34 months. OS was 90.5% at 36 months and 66.7% at 60 months with a median value of 76 months in the IDH1-2 mutated/1p19q codeleted subgroup, while OS was 66.7% at 36 months and 50% at 60 months with a median value of 60 months in the IDH1-2 wild-type subgroup. Responses were higher in MGMT methylated patients. Seizure improvement was achieved in 29/34 patients (85%): 17/33 (52%) patients at 12 months and 18/29 (62.1%) at 24 months were seizure-free. Time to maximal seizure response was earlier than that observed on MRI (3 vs 6 months). Conclusions: Dose-dense TMZ has shown a significant activity in terms of tumor and seizure control, especially in IDH1-2 mutated/1p19q codeleted patients. Seizure reduction could represent an early indicator of response to chemotherapy and maybe predict the duration of response. Clinical trial information: 2007-000386-38.